UI/UX Design of the “PrintOn!” Printing Services Marketplace for UMKM Photocopying and Printing Businesses Using the User Centered Design Method - Windy Fadhilah Susanti; Seftin Fitri Ana Wati; Tri Luhur Indayanti Sugata (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
UMKM in the photocopy and printing sector faced several obstacles when managing orders through messaging platforms. Customer messages were often difficult to identify due to the absence of names or profile photos, and lengthy, unclear texts further complicated communication. The use of multiple platforms such as social media and email required manual checking, which delayed response times. This study aimed to design a user interface and user experience (UI/UX) for a printing service marketplace application to improve the service process for UMKM. The design process followed a human-centered design approach, beginning with literature studies, user context identification through interviews with 15 respondents, and user needs analysis using empathy maps, personas, and affinity diagrams. Solutions were developed through user flow mapping, information architecture, and prototyping using Figma. Evaluation was conducted using usability testing via Maze, the System Usability Scale, and heuristic evaluation by five expert evaluators. The findings indicated issues in areas such as consistency and aesthetic minimalism, which received high severity ratings. After iterations, customer usability scores improved from 67.5 to 82.8 and provider scores from 78.5 to 80.5. These results demonstrated that the final "PrintOn!" application design met usability standards and enhanced user experience, making it ready for implementation.